Factors driving changes in water conservation function from a geospatial perspective: case study of Jilin Province - Gao, Teng; Li, Yuchen; Zhao, Chunzi; Chen, Jingping; Jin, Ri; Zhu, Weihong (Frontiers in Ecology and Evolution, 2023)
Jilin Province in China borders other countries in Northeast Asia and is a complex ecosystem of transboundary rivers, varying terrains, and climates, which provides vital freshwater resources to the neighboring countries. Water conservation is one of the ecosystem service functions and is of great significance to maintaining sustainable development of water resources and ecological security. In this study, we analyzed the water conservation function and its variations in Jilin Province from 2000 to 2020 using the InVEST model. Furthermore, we examined the dominant factors governing spatial distribution of the changes in water conservation function over the past two decades using geographical detectors. In addition, a multi-scale geographic weighted regression model was adopted to investigate spatial differences and characteristics of individual drivers across different spatial scales. The study revealed a number of findings. First, between 2000 and 2020, average water conservation in Jilin Province increased by 46.12% overall from 87.14 mm/m2 to 127.28 mm/m2. Second, compared with land use change, climate change had a greater influence on water conservation. However, in some areas, the opposite was true, and the combined impact of both factors was more substantial on water conservation than when each acted independently. Third, except for temperature, the correlation between each driving factor and the change in water conservation function exhibited spatial variations, and the characteristics of each factor also varied across different spatial scales. In the study site, variations in water conservation were positively correlated with forest and grass coverage and negatively correlated with cultivated land and urban-rural and industrial-mining land. This study provides new insights for exploring the driving factors of changes in water conservation function and imparts a more appropriate basis for government agencies to make decisions about ecological and environmental protection and optimization of ecosystem management.